Sensory recovery in medial plantar flaps for posterior heel defects as a guide to rehabilitation regime - Dipankar Mukherjee; Monali Patole Mukherjee; Santu Kumar Chejara; Akshay Kapoor; Debarati Chattopadhyay (Asian Journal of Medical Sciences)
Background: For reconstruction of the foot, a medial plantar flap is used to provide a like-for-like replacement. The problem at present seems to be that there are no objective criteria to guide the rehabilitation regimes of these patients. The arbitrary rule that the patient may begin weight-bearing after 4 weeks of surgery may not be applicable to all patients as the etiology of the defect and time for recovery may differ.